Non-functional properties in service oriented architecture : requirements, models and methods - Milanovic, Nikola. (Information Science Reference, 2011)
"This book offers a selection of chapters that cover three important aspects related to the use of non-functional properties in SOA: requirements specification with respect to non-functional properties, modeling non-functional properties and implementation of non-functional properties"--Provided by publisher.